A Development Of Optimal Buffer Allocation Determination Method For Μ-Unbalanced Unpaced Production Line - Ismail, Mohd Shihabudin (2009)
This research deals with a buffer allocation problem in an unpaced (asynchronous) μ-unbalanced production line. Kajian ini membincangkan masalah peruntukan pemampan di dalam talian pengeluaran tidak melangkah dengan ketidakseimbangan-μ .